Furniture design in Temerloh and Jengka / Nor Azura Mohammed Shariff and Noorshashillawati Azura Mohammad - Mohammed Shariff, Nor Azura; Mohammad, Noorshashillawati Azura (2011)
The intention of this paper is to describe the finding of research on furniture design in Malaysia by owner companies and customers. It aims to anticipate what the future holds and how designers may respond accordingly. The paper focuses on a research project which examined the responses of respondent/customer users to various aspects of furniture design. Several of questions were taken from two companies randomly selected subject and 100 copies of questionnaires are distributed among the respondents/ customers. Data obtained from Ilham Design Furniture Company and Courts Mammoth Company.